Full-color emissive bidirectional needle-like nano-tips of the hybrid of Tb/Eu-Metal organic frameworks @ inorganic halide perovskite for multifunctional applications - Kachhap S.; Singh A.K.; Singh S.K. (My University, 2025)
A multifunctional metal-organic framework (Tb/Eu-MOF) interfaced with an CsPbCl1.5Br1.5 is developed. The self-assembled Tb/Eu-MOF has a bi-directional needle-like morphology. The successful formation of the CsPbCl1.5Br1.5 inside the porous Tb/Eu-MOF is evidenced by the characteristic absorption edge and characteristic PL emission of CsPbCl1.5Br1.5. PL studies show the unilateral energy transfer from Tb3+ to Eu3+. The CsPbCl1.5Br1.5 does not show any optical interaction with the other two emitting centers (Eu3+ and Tb3+) and emits only by its characteristic excitation. The cool white light emission is achieved by CsPbCl1.5Br1.5@ Tb/Eu-MOF in PMMA matrix-coated UV-LED chip. The CIE coordinate, CCT, CRI, Vis., and color purity are calculated. Further, the excitation wavelength-dependent emission spectrum spans from blue to yellowish-red region opens the potential of the material for anti-counterfeiting application. The letter "W" encrypted on four different substrates exhibit momentous color change under different excitation wavelengths and show excellent stability over time in ambient conditions. © 2025